2018
DOI: 10.1182/bloodadvances.2017014050
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial tumor suppressor p53 is essential for venous thrombus formation in aged mice

Abstract: Key Points• Deletion of p53 in endothelial cells prevents venous thrombosis in aged, but not in adult, mice.• Neutralization of heparanase in aged mice using TFPI2 peptides restores the thrombotic phenotype of adult mice. End.p53-KO mice were protected from vein thrombosis. Analysis of primary endothelial cells from aged mice or human vein endothelial cells after induction of replicative senescence revealed significantly increased early growth response gene-1 (Egr1) and heparanase expression, and plasma factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…76 Our study in mice shows the importance of p53 for the risk of thrombosis in vivo, especially in states of endothelial p53 upregulation, such as in increased age. 77 In this study, we could show that aging in mice was associated with p53 overexpression and apoptosis in endothelial cells lining the inferior vena cava (IVC). Moreover, aged mice developed more frequent and larger venous thrombi after being subjected to subtotal IVC ligation, whereas aged mice with endothelial-specific p53 deletion were protected from venous thrombosis.…”
Section: Novel Endothelial-derived Mediators Of Thrombosismentioning
confidence: 94%
See 1 more Smart Citation
“…76 Our study in mice shows the importance of p53 for the risk of thrombosis in vivo, especially in states of endothelial p53 upregulation, such as in increased age. 77 In this study, we could show that aging in mice was associated with p53 overexpression and apoptosis in endothelial cells lining the inferior vena cava (IVC). Moreover, aged mice developed more frequent and larger venous thrombi after being subjected to subtotal IVC ligation, whereas aged mice with endothelial-specific p53 deletion were protected from venous thrombosis.…”
Section: Novel Endothelial-derived Mediators Of Thrombosismentioning
confidence: 94%
“…115 Although still at the experimental stage, we and others could establish the efficacy of potential novel therapeutic strategies, such as TFPI2 peptides, for their potential to limit the extent of acute venous thrombosis in mice. 77,83,84…”
Section: Antithrombotic Therapeutic Strategies Targeting the Endothelmentioning
confidence: 99%
“…Expression of p53 also stimulates PAI-1 secretion in endothelial cells (among other genes in endothelial cells). The effect of reducing fibrinolysis outweighs that of increasing collagenolysis, because overexpression of p53 increases thrombus size [227], and in aged mice an endothelial knockout of p53 protects against DVT [228]. However, genetic or pharmacologic inhibition of p53 impairs DVT resolution in younger adult mice, whereas the p53 agonist quinacrine accelerates this resolution [229].…”
Section: Collagenolysismentioning
confidence: 99%
“…Recently, Bochenek et al showed in a model of endothelial senescence that inhibition of heparanase activity using the TFPI-2 peptides prevented enhanced venous thrombus formation in aged mice and restored it to the thrombotic phenotype of control adult mice. 62 Thus, heparanase inhibition could also potentially affect the course of aging in endothelial cells.…”
Section: Inhibition Of Heparanase Procoagulant Activitymentioning
confidence: 99%